2014
DOI: 10.1002/anie.201306746
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Single‐Crystal‐to‐Single‐Crystal Photochemical Formation and Thermal Cleavage of a Cyclobutane Ring

Abstract: A [2+2] cycloaddition reaction has been observed in a number of solids. The cyclobutane ring in a photodimerized material can be cleaved into olefins by UV light and heat. The high thermal stability of the metal-organic salt K2SDC (H2SDC = 4,4'-stilbenedicarboxylic acid) has been successfully utilized to investigate the reversible cleavage of a cyclobutane ring. The two polymorphs of K2SDC undergo reversible cyclobutane formation by UV light and cleavage by heat in cycles. Of these, one polymorph retains its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 31 publications
3
47
0
2
Order By: Relevance
“…The 1D CP chains can be disrupted exposing it to HCl vapors as a clear color change from blue to yellow occurs within 0.5 h. SC-XRD allowed unambiguously to determine the structure of the new phase which resulted to be a nonporous second sphere adduct of distorted tetrahedral [CuCl 4 ] 2− dianions and [imH 2 ] + cations. By thermal treatment at 363 K for 3 h, the second sphere adduct can be transformed to a new 1D CP (11 ) following the release of HCl upon bond Cu-Cl and N-H cleavage and formation of Cu-N coordination bonds. The disruption and formation of chemical bonds can occur also spontaneously but with longer periods of time (i.e., several weeks).…”
Section: Thermally Induced Single-crystal-to-single-crystal (Scsc) Rementioning
confidence: 99%
See 1 more Smart Citation
“…The 1D CP chains can be disrupted exposing it to HCl vapors as a clear color change from blue to yellow occurs within 0.5 h. SC-XRD allowed unambiguously to determine the structure of the new phase which resulted to be a nonporous second sphere adduct of distorted tetrahedral [CuCl 4 ] 2− dianions and [imH 2 ] + cations. By thermal treatment at 363 K for 3 h, the second sphere adduct can be transformed to a new 1D CP (11 ) following the release of HCl upon bond Cu-Cl and N-H cleavage and formation of Cu-N coordination bonds. The disruption and formation of chemical bonds can occur also spontaneously but with longer periods of time (i.e., several weeks).…”
Section: Thermally Induced Single-crystal-to-single-crystal (Scsc) Rementioning
confidence: 99%
“…The use of external stimuli to induce solid state reactivity can be studied by different approaches such as light induced reactivity [9][10][11][12][13], mechanical reactivity [14][15][16], high pressure reactivity [17,18], thermally induced reactions [19][20][21][22], or a combination of temperature and other aspects that might influence the reaction [23]. High temperature synthesis in MOMs is very appealing as often many synthesized materials obtained as kinetic products can be transformed into more stable thermodynamic structures upon heating.…”
Section: Introductionmentioning
confidence: 99%
“…

The cyclobutane cleavager eactioni sa ni mportant process and has received continuous interest.H erein, we demonstrate the visible laser-driven cleavage reactiono fc yclobutane in crystal form by using in situ Ramans pectroscopy.S ilver(I)c oordination-induced strain and thermale ffects from the laser irradiation are the two main driving forces for the cleavage of cyclobutanec rystals. [3][4][5][6][7] It has been reported that pyridyl-substituted cyclobutane coordinated with metallic ions can undergo isomerization/cleavage reactions upon thermalt reatment, [8][9][10][11] and recently,m etal-organic organopolymeric hybrid frameworks have been produced by using [2+ +2] cycloaddition reactions. in the case of thymine cyclobutane dimer), is av ery important reaction process and has received wide-spread interest.

…”
mentioning
confidence: 99%
“…[1,2] Thermally induced ion or molecule movement at the molecular level can lead to unit-cell dilation, crystal structure altering, and cyclobutanei somerization/cleavage. [3][4][5][6][7] It has been reported that pyridyl-substituted cyclobutane coordinated with metallic ions can undergo isomerization/cleavage reactions upon thermalt reatment, [8][9][10][11] and recently,m etal-organic organopolymeric hybrid frameworks have been produced by using [2+ +2] cycloaddition reactions. [12,13] Besidesc onventional heat resources, laser irradiation can also be applied to induce cleavage reaction.…”
mentioning
confidence: 99%
“…127 Solids that undergo SCSC transitions are relevant to applications in areas such data storage, sensors, and shape memory. [128][129][130] Halogen bonds, in contrast to hydrogen bonds, often involve rigid interacting partners such as iodopolyfluorophenyl groups. The energies of halogen bonds based on rigid groups have been reported to exhibit a higher dependence on angle versus hydrogen bonds, 118,131 which means that halogens bonds can be expected to be less tolerant to autonomous and collective movements of the constituent atoms in constrained media such as crystals.…”
Section: Fluorine In Crystal Engineering and Dissertation Overviewmentioning
confidence: 99%